CONCEPTUAL BASIS OF THE CONCEPT OF SPATIAL ORGANIZATION OF BODY OF CHILDREN 6-10 YEARS WITH SENSOR SYSTEMS DEPRIVATION IN THE PROCESS OF PHYSICAL EDUCATION - Svetlana Savlyuk (Фізичне виховання, спорт і культура здоров’я у сучасному суспільстві, 2017)
Topicality. Physical education process in special boarding schools for children with sensory systems deprivation (SSD) has not yet been sufficiently studied and developed therefore requires the implementation of new tools, forms and methods aimed at preventing and correcting violations of spatial organization of body (SOB) of children with SSD that has become a prerequisite for the substantiation and development of the author's concept. Objectives of the study: determine the structure and content of the concept of the spatial organization of the body of children 6-10 years old with SSD in the physical education process in special boarding school. Research Results. The concept of the study is the provision for the formation of the correct spatial organization of the body of children aged 6–10 years from the DSS, taking into account individual abilities, types of impaired posture, indicators of physical condition and the use of subtle differentiation, depending on the degree of sensory impairment, secondary layers, concomitant diseases of children 6-10 years old with DSS, which significantly affect  their psychophysical and psycho-emotional state, adaptation and social integration of children with special needs in the society of healthy peers. Conclusions. The basic constituents of the concept of the formation of SOB of children with SSD are its prerequisites, conceptual approaches, conceptual foundations, technology of prevention and correction of violations of SOB of children with SSD, comprehensive diagnostics of components of SOB of children, programs for prevention and correction of infringements of SOB of children 6–10 years with VD and HD, control and criteria of its effectiveness.